Figurative language! an educational autobiography / Nur Najwa Maisarah Nasition and Nurul Atiqah Abd Hamid - Nasition, Nur Najwa Maisarah; Abd Hamid, Nurul Atiqah (Academy of Language Studies, 2023)
Creative writing is a known expressive form of writing in literature and carries an invaluable significance in the field of education. Possessing creative writing skills allow students to expand on their creativity, therefore allowing their cognitive thinking skills to develop. The present paper discusses the importance of creative writing and figurative language, and language students’ perception on the matter. For this, research was carried out in the form of a Google Form questionnaire. The findings revealed that there is a lack of educational reading material focusing on creative writing amongst the students of LG120 of UiTM Cawangan Melaka. Thus, the end goal of the research is to come up with an academic autobiographic E-book focusing on creative writing to be used as a leisure reading material for LG120 students. The project intends to expose the many components of figurative language in creative writing to readers and help them understand better, fully taking advantage of the ease of convenience provided by E-books in the current era’s ever-evolving educational materials.